Peningkatan Pemahaman Keislaman Masyarakat melalui Pengabdian Berbasis Ushuluddin di Desa Pasilian, Tangerang: Enhancing Community Understanding of Islamic Teachings Through Ushuluddin-Based Community Service in Pasilian Village, Tangerang - Muhammad Ghifari; Diski Farihatul Anam; Nuriya Safitri; Muhammad Asgar Muzakki (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This community service was motivated by the limited understanding of Islamic teachings among the community of Pasilian Village, Tangerang Regency, particularly regarding moral values in social life. The partners faced declining intensity of moral education within families and the influence of digital media on children's behavior. The objective was to improve Islamic understanding through an Ushuluddin-based approach emphasizing Qur'anic and Hadith-based moral values. The participatory method involved 85 participants including religious leaders, mosque administrators, parents, and children. Activities included Hadith study sessions, Mobile Qur'an, TPA (Qur'an education for children), Islamic spiritual activities (Rohis), and regular Yasin recitations on Friday nights over two months (June–August 2024). Evaluation used pretest-posttest, participatory observation, and interviews. Success indicators were a minimum 30% increase in understanding scores and 75% participation rate. Results showed the average moral understanding score increased from 54.2 to 81.6 (50.6% increase). Participation reached 82%. Behavioral changes included improved discipline in congregational prayers and polite language use. This service contributes to building ethical awareness in the community and provides a replicable Ushuluddin-based service model. Recommendations include establishing village religious cadres.